Efficacy of Event MON 87460 in drought-tolerant maize hybrids under optimal and managed drought-stress in eastern and southern africa - Obunyali, Caleb O; Pillay, Kiru; Meisel, Barbara; Ndou, Eric N; Mashingaidze, Kingstone; Sserumaga, Julius Pyton; Asea, Godfrey; Mwimali, Murenga; Tende, Regina; Beyene, Yoseph; Mugo, Stephen; Okogbenin, Emmanuel; et al. (Elsevier B.V, 2014)
Abstract Frequent drought events due to climate change have become a major threat to maize (Zea mays L.) production and food security in Africa. Genetic engineering is one of the ways of improving drought tolerance through gene introgression to reduce the impact of drought stress in maize production. This study aimed to evaluate the efficacy of Event MON 87460 (CspB; DroughtGard®) gene in more than 120 conventional drought-tolerant maize hybrids in Kenya, South Africa, and Uganda for 3–6 years under managed drought-stress and optimal conditions and establish any additional yield contribution or yield penalties of the gene in traited hybrids relative to their non-traited isohybrids. Germplasm used in the study were either MON 87460 traited un-adapted (2008–2010), adapted traited DroughtTEGO® (2011–2013) or a mix of both under confined field trials. Results showed significant yield differences (p < 0.001) among MON 87460 traited and non-traited hybrids across well-watered and managed drought-stress treatments. The gene had positive and significant effect on yield by 36–62% in three hybrids (CML312/CML445; WMA8101/CML445; and CML312/S0125Z) relative to non-traited hybrids under drought, and without significant yield penalty under optimum-moisture conditions in Lutzville, South Africa. Five traited hybrids (WMA2003/WMB4401; CML442/WMB4401; CML489/WMB4401; CML511/CML445; and CML395/WMB4401) had 7–13% significantly higher yield than the non-traited isohybrids out of 34 adapted DroughtTEGO® hybrids with same background genetics in the three countries for ≥ 3 years. The positive effect of MON 87460 was mostly observed under high drought-stress relative to low, moderate, or severe stress levels. This study showed that MON 87460 transgenic drought tolerant maize hybrids could effectively tolerate drought and shield farmers against severe yield loss due to drought stress. The study signified that development and adoption of transgenic drought tolerant maize hybrids can cushion against farm yield losses due to drought stress as part of an integrated approach in adaptation to climate change effects.
Keywords: CspB gene; DroughtGard®; DroughtTEGO® hybridsGene efficacy; Managed drought-stress; MON 87460 Event; Optimum-moisture; Traited transgenic hybrids; Yield penalty; Zea mays